Perspectives of post-commencement financiers regarding their voting rights on a business rescue plan - Van Niekerk, Larisa (University of Pretoria, 2024)
Post-commencement financiers provide a lifeline to companies under business rescue and these financiers have their best interest in the survival of these companies. Should it be that the business rescue plan is unsuccessful, the chances are that the post commencement financiers will be the largest creditors. In Wescoal Mining (Pty) Ltd v Mkhombo NO, a dispute arose regarding the appropriate adoption of a business rescue plan during the meeting. One critical legal issue was whether the Companies Act bestows voting rights exclusively to the company's creditors who existed at the initiation of business rescue, or if creditors accruing after the commencement may also partake in voting on the plan. Following an assessment by Judge Wilson, it was established that only creditors with claims predating the commencement were eligible to participate in the voting process. Subsequently, Judge Wilson believed that section 135 of the Companies Act places post-commencement financiers as creditors in a different class and provides for their protection and interests in a different way. Against this background, the dissertation evaluates the position of post-commencement creditors when it comes to voting on a business rescue plan.
Keywords: Business rescue; Company law; Creditors; Insolvency; Insolvency law; Life-line; Post-commencement creditors; Post-commencement finance

Climate change and international investment law : lessons from Africa's investment treaty practice - Mogashoa, Lebogang Paul (University of Pretoria, 2024)
This dissertation critically analyses new generation continental, regional and bilateral investment treaties in Africa with the aim to explore enhancements that could be made thereto in order to enable African citizens to hold investors accountable for investment-related climate change issues in Africa. The main research question answered in the dissertation is: to what extent does African investment treaty practice incorporate climate change-related provisions and investor accountability for climate change. The dissertation analysed traditional investment treaties, particularly noting their silence on climate change and investor accountability, and their partiality to investor protection. Using the AfCFTA Investment Protocol as an anchor alongside other new generation continental, regional and bilateral investment treaties in Africa, it discusses a fundamental contemporary shift in African investment treaty practice towards ensuring sustainable investments and greater investor accountability for sustainability in Africa. It also explores the various limitations in these new generation investment treaties that still make investor accountability. In the end it proposes reforms to the Investor-State Dispute Settlement provisions of these investment treaties to recognise citizen-led arbitral claims against investors, utilising the Hague Rules on Business and Human Rights as the procedural infrastructure for handling arbitration of such claims.
Keywords: AfCFTA; African Continental Free Trade Area; Climate change; ISDS; Investment treaties; Investments; Investor-State Dispute Settlement

The relationship between the business rescue practitioner and the directors of the company - Mokoka, Neo (University of Pretoria, 2024)
This dissertation on the relationship between the business rescue practitioner and the directors of the company under business rescue. In essence, this dissertation investigates whether a conflict arises between the duties, roles and powers of the business rescue practitioner and those of directors of the financially distressed company. The aim of this dissertation is to study what are the limitation on duties, roles and powers of directors of the company as a result of the appointment of the business rescue practitioner and the extent thereof. In achieving the above objective, this dissertation commences with setting out the background of business rescue proceedings in South Africa by analysing provisions of Chapter 6 of the Companies Act 71 of 2008 which has introduced “a new corporate rescue procedure” in South Africa, being business rescue. The focus is on provisions dealing with duties, roles and powers of directors in the ordinary course as set out in section 66, 75 to 77 of the Act. The focus then shifts to the provisions dealing with the commencement of business rescue proceedings, the appointment of the business rescue practitioner and his duties, roles and powers. In order to establish whether a conflict truly exists between the duties, roles and powers, various sources dealing with this issue are considered. In order to assess whether there are solutions in dealing with the conflict and/or limitation that arises, this dissertation includes a comparative study on selected foreign jurisdictions dealing with the interaction between the board of directors and business rescue practitioner are considered. In particular, this dissertation considers corporate rescue mechanisms in the Commonwealth of Australia, the United Kingdom and the United States of America. The purpose of the comparative study is to determine which lessons can be learned from the practices in the aforementioned jurisdictions. The overall objective of this study is to determine how the South African legal framework pertaining to the interaction between directors and business rescue practitioners can be enhanced.
Keywords: Business rescue; Business rescue practitioner; Companies Act 71 of 2008; Comparative study; Duties of directors; Limitations on powers; Powers of directors; Roles of directors; US bankruptcy code

Theories on the nature and purpose of the company and their implications for corporate governance - Ramalho, Anna Francina (University of Pretoria, 2024)
Despite the emergence of corporate governance as a formal discipline more than thirty years ago, the proliferation internationally of scholarly work on the topic and its formal regulation over this period, the scope, definition and direction of corporate governance remain contested. Company theories could potentially assist in this regard but have been inconsistent in their explanations of the both the means and ends of corporate governance. This has led to scepticism about the efficacy of theories to illuminate the phenomena associated with companies and company law. Notwithstanding, theory is critical as it makes explicit what is implicit in policymaking by regulators, as well as in the behaviour and decision-making by corporate actors, so that regulation and decisions are transparent for analysis and evaluation. The study, therefore, set out to provide a synthesis and doctrinal analysis of the main theories on the nature and general purpose of corporations in historical context. It was found that objections can be raised against all of these theories to a greater or lesser extent for inaccurate portrayal of the law, limited explanatory power and detachment from the real word. This study shows that corporate theories are a product of the settings in which they have developed and consequently none of these theories represents a universal or absolute truth, nor are they an inevitability due to widespread adoption and use. This leaves room for new formulations of the corporate form and its purpose fit for today’s context with its political, social and environmental challenges. This dissertation also includes further directions for theoretical exploration.
Keywords: Contractarianism; Corporate governance; Entity theories; Shareholder primacy; Stakeholder theories

Selected problem areas pertaining to the removal of directors from office - Shange, Thandokuhle Wandile (University of Pretoria, 2024)
This paper constitutes a composite analysis of the legal framework and procedures for removing directors and the key challenges presented by the framework. It achieves this by looking at four legal questions: Firstly, it looks into what is the legal framework for director removal in South Africa, secondly, it delves into the challenges and/or uncertainties presented by this process, and further explores if there are any possible learnings South Africa can learn from foreign jurisdiction.
Keywords: Companies Act 2008; Comparative company law; Director removal; Director’s right; Judicial review; Section 71

Proposed legal reforms to protect South Africa's informal social security - Zeelie, Robin Erin (University of Pretoria, 2024)
Informal social security is a non-governmental form of social security between kin and/or community members and is a prevalent practice in South Africa. The question this dissertation analyses is whether the South African government fails in its constitutional duty to protect and advance informal social security. The dissertation limits itself to analysing cash transfers through social grants, and social insurance in the Unemployment Insurance Act and the Compensation for Occupational Injuries and Diseases Act. This dissertation delineates its definition of informal social security, historically contextualises its practice, and explains the contemporary formal social security framework. This dissertation finds five prominent shortcomings in the formal framework, and that these shortcomings have a profoundly negative, weakening effect on informal social security, as the more people who rely on informal mechanisms, the less it can respond to needs arising from life contingencies, shocks, and risks. The dissertation concludes by analysing three legal reform proposals the state can implement: extending existing social insurance frameworks to those in the informal sector, promoting cooperatives as a formal platform for the informal, and the basic income grant.
Keywords: Basic income grant; Cooperatives; Duty; History; Informal social security; Republic of South Africa; Social assistance; Social security

'Banking' on artificial intelligence to enhance bank risk management - Chiba, Mayuree (University of Pretoria, 2024)
This dissertation investigates the impact of digital transformation on risk management within the banking sector, emphasizing the integration of artificial intelligence (AI) in enhancing operational risk management. It examines key research questions about how digitisation reshapes risk management practices, the extent to which South African banks align with international standards, and the role of AI in advancing these frameworks. The study finds that AI holds substantial potential to improve risk management, particularly in managing operational risks, while underscoring the indispensable role of human oversight. Ultimately, this shift toward a more AI-driven, adaptive approach marks a pivotal evolution in the financial sector, suggesting that the future of risk management can indeed rely on AI's transformative capabilities.
Keywords: Artificial Intelligence; Bank; Inteligência artificial; Intelligence Artificielle; Operational risk; Risk management

Facilitating Trade through Rules of Origin: A Consideration of the African Continental Free Trade Area - Okoroma, Blessing Ijeoma (University of Calgary, 2024)
Rules of origin play a pivotal role in free trade agreements. Apart from serving as a tool to distinguish goods by determining the nationality of a product, rules of origin have the capacity to increase trade relations or deter it. Of course, it is the hope of any viable state to increase profitable trading relations, and if rules of origin can help with that, it becomes expedient to fully understand how these rules of origin operate. In Africa, we see rules of origin being implemented amongst the Regional Economic Communities (RECs), but this has come with many struggles. In fact, low intra-African trade can be narrowed down to complex rules of origin regimes deployed in regional agreements in Africa. As of date, the major RECs have each implemented different rules of origin, leading to the co-existence of conflicting rules of origin across Africa. This non-uniformity in the rules of origin regimes in Africa has resulted in low continental trade in Africa. As such, these RECs have not yielded the expected increase in intra-African trade. With the creation of the African Continental Free Trade Area (AfCFTA), which currently doubles as the latest and largest FTA in Africa, it is expected that better rules of origin will be deployed to mitigate the existing intra-African trade deficits. This thesis thus deploys a doctrinal approach in determining whether AfCFTA’s rules of origin are positioned to achieve greater intra-African trade. Consequently, this thesis uncovers some lapses in AfCFTA’s rules of origin and calls for harmonization of all the rules of origin in Africa and recommends a possible amendment to Article 19 of the Agreement establishing AfCFTA to accommodate the intended harmonization.
Keywords: African Continental Free Trade Area; Free Trade Area; Rules of Origin

Taxpayer Confidentiality : implications of the tax secrecy provisions regarding illegal miners - Kgobe, Kgothatso (University of Pretoria, 2024)
Taxpayer confidentiality and its implications (if any), on illegal miners

Lessons for insolvency law from the emoluments attachment order experience - Grobler, Frederik (University of Pretoria, 2024)
Section 23(5) of the Insolvency Act poses an interesting challenge, namely vesting a portion of an insolvent’s post-sequestration income in the trustee of the insolvent estate without infringing on the insolvent’s constitutional rights. The income earned by the insolvent during sequestration is in general excluded from his estate and does not vest in the trustee, unless the Master determines that a portion of the insolvent’s income will not be required to maintain the insolvent and his dependents. In such a case, only the portion deemed to be surplus to requirements will be included in the insolvent estate and will vest in the trustee. The question of what role the insolvent’s income should play during the sequestration process, and therefore how section 23(5) should be interpreted and applied, has vexed the courts and numerous practical and constitutional issues arise. This study examines the application and shortcomings of section 23(5) during the administration phase of the sequestration process. It then explores the lessons learned during the recent constitutional scrutiny and subsequent amendment of the emoluments attachment process. Lastly, recommendations are made for possible law reform of section 23(5).

The development of explicit deposit insurance schemes in selected countries in Southern Africa - Moloi, Mbakiso Ndumiso (University of Pretoria, 2024)
This dissertation explores the evolution of explicit deposit insurance schemes (EDIS) in Southern African countries. It emphasises the important role of banks in the economy and their vulnerability to failures despite prudential requirements and supervision. Financial safety nets are essential for failing banks, and deposit insurance is the primary mechanism to protect depositors and maintain financial system stability in the event of a bank's failure. Originating in 1933 with the establishment of the Federal Deposit Insurance Corporation in the United States of America during the Great Depression, EDIS has become a global standard. Southern Africa, with its developing financial sector, faces many challenges including bank failures, causing depositors to lose funds. The region's high interconnectedness increases the threat of contagion if parent banks fail. The absence of deposit insurance raises the likelihood of fiscal authorities succumbing to political pressure to bailout failing banks during crises as seen during the 2007-09 Global Financial Crisis (GFC). The GFC prompted the International Association of Deposit Insurers and the Basel Committee on Banking Supervision to establish the Core Principles for Effective Deposit Insurance Systems. Issued in June 2009, these principles are used by jurisdictions as a benchmark for assessing the quality of their deposit insurance systems and identifying gaps in their deposit insurance practices. This research aims to evaluate international best practice standards for EDIS and extract lessons from the establishment of EDIS in the USA to address gaps in the implementation of deposit insurance schemes in Southern African countries. Examining ten Southern African countries, this research investigates varied progress in EDIS adoption. Case studies, particularly Zimbabwe as a pioneer of EDIS in the region and Namibia as a recent entrant, help to identify gaps and opportunities for enhancing deposit insurance frameworks in the region.

Rethinking Environmental Obligations in Corporate Insolvencies: What New Role for Lenders? - Ebegbodi, Daniel Onyeje (University of Calgary, 2024)
Environmental reclamation obligations are statutory mechanisms designed to regulate environmental protection by corporate entities. Bankruptcy laws on the other hand are meant to offer insolvent corporations an opportunity to reorganize their affairs, satisfy creditors claims and make a fresh start. In practice, the application of bankruptcy laws can undermine key environmental reclamation objectives, leading many to ask whether a corporation undergoing restructuring with significant outstanding environmental reclamation obligations should be able to commence bankruptcy proceedings to satisfy creditors’ claims? By employing the doctrinal and comparative research methodologies, this research interrogates that inquiry. It argues that, despite the importance of bankruptcy protection for corporations undergoing financial distress, environmental protection should be paramount. Although sustainable finance (SF) instruments have been deployed by banks to enable creditors to mitigate environmental concerns in their investments, the persistent recurrence of environmental reclamation issues in the oil and gas sector particularly during insolvencies, underscores the need for financial investors to strengthen their investment policies to reflect best practices providing the desired protection for the environment. The research finds that, although SF and environmental, social and governance (ESG) approaches, are commendable, they are insufficient in instilling adequate regulatory impact on the environment compared to judicial control offered by the courts. The thesis concludes that whilst judicial control mechanism is not without concerns, with government’s deliberate financial policy and judicial control to complement SF and ESG efforts, ESG and SF mechanisms can be strengthened to compel greater significant influence on best practices in lending.

Aspects of substantial compliance and strict compliance as applied to demand guarantees - Sikobi, Nkanyiso (University of South Africa, 2024)
Demand guarantees are essential for purposes of commerce and are used to secure the performance of the contractor. South African courts have held that demand guarantees are akin to letters of credit. Despite the independent nature of demand guarantees to the underlying contract, in circumstances where the beneficiary has made a fraudulent claim, the guarantor may dishonour the demand or claim. South African courts have indicated that if the underlying contract is illegal, courts may intervene by granting an interdict to stop payment under the guarantee. The South African law recognises traditional guarantees (often called suretyship) where the beneficiary, when making a demand or claim, must demonstrate liability on the part of the contractor. There are instances where courts have held that guarantees were of a nature akin to suretyship. In South Africa, parties entering into a demand guarantee contract are subject to the common law of contract. The Uniform Rules for Demand Guarantees, adopted by the International Chamber of Commerce, are only applied by explicit reference in the demand guarantee failing which such rules do not apply. Non-implementation of these rules has resulted in rigorous litigation in the recent years on this subject-matter. A demand must be supported by documents and require strict conformity. However, strict compliance with the prerequisites of the demand guarantee has not been applied consistently in South Africa. South African courts have recently been applying substantial compliance, in certain circumstances finding that a term in a guarantee is just directory and not obligatory. Furthermore, on many occasions, courts have deviated from strict compliance holding that a term in a guarantee does not make commercial sense thus such term is not mandatory. In this way, courts apply the most business-sensible interpretation when interpreting demand guarantees.
Keywords: Autonomous; Beneficiary; Contractor; Demand guarantees; Demand or conditional guarantee; Documentary letters of credit; Employer; First written demand; Fraud and illegality exception; Guarantor; Independence; Performance guarantees; Security for performance; Strict compliance; Substantial compliance; Suretyship; Underlying contract; Uniform rules for demand guarantees

The legal framework regulating the duties of insurance intermediaries - Sithole, Eugine (University of Pretoria, 2024)
In South Africa, before the Financial Advisory and Intermediaries Services Act (FAIS Act) and other insurance laws came into existence, intermediary services regarding the rendering of insurance products have always been regulated by the law of agency and mandate. This means that the Roman-Dutch principles provided for the standards to which the conduct of intermediaries was to comply with when rendering insurance services. The mandate of intermediaries in terms of the Roman-Dutch Principles also included the fact that they had to act with care, skill and in good faith. When the FAIS Act came into operation, it introduced several detailed rules and minimum standards for insurance intermediaries to comply with, and these minimum standards are not limited to qualifications, experiences and characteristics of honesty and integrity that an intermediary must comply with, but they also stipulated in detail what an intermediary must do when discharging insurance intermediary duties. The FAIS Act is the leading legislation when it comes to the regulation of intermediary services. The FAIS Act, under section 16, provides for a General Code of Conduct for Authorised Financial Services Providers and their Representative (GCC), which contains a set of rules that are applicable to all intermediaries. These rules under the GCC are aimed at ensuring that insurance customers are provided with material facts that will enable them to make a prior informed decision and that their reasonable financial needs concerning insurance products will be carefully considered so that they can be provided with a product that will be suitable to satisfy their needs. Furthermore, in terms of South African laws and practices, intermediaries play an essential role in the creation of legally binding insurance contracts. Insurance businesses are concluded through intermediaries. Considering that many insurance companies are juristic persons, and they can only conduct business by means of human agents, insurance laws make it compulsory for intermediaries to have skills, knowledge, and experience regarding insurance products that they are rendering to insurance customers. It is commonly believed that intermediaries with skills, knowledge and experience, they always act in the best interest of the client, and they ask relevant questions to assist the clients to disclose all material facts, and they always make sure that material facts are clearly communicated/disclosed to the insurer and insured to avoid future conflicts. The legal framework placed a duty on the intermediary to assist the insured to disclose all material facts and to explain all clauses contained in the insurance contract which may lead to the insurer repudiate its liability. Furthermore, an intermediary is at all material times expected to first consider the financial situation of the potential insured before determines a cover that will be best suitable for the insured’s needs. However, despite the best guidelines outlined by applicable insurance laws and regulations, mistakes are still being made by intermediaries, which lead to insurance customers to suffer the consequences of impractical intermediary services, and that has resulted in numerous complaints, legal disputes, debarments, and other regulatory actions. As a result of intermediaries’ continuous misconduct, insurers have been repudiating claims, and it has created a presumption that insurers conduct businesses to enrich themselves instead of protecting the interests of their customers as required by regulating legal framework. Therefore, so many people have lost confidence in the insurance industry due to unlimited court cases and complaints arising from misconduct or omissions of intermediaries, such as their failure to disclose material facts to the parties. Once it is found that material facts were not fully disclosed between the insurer and insured, both parties would have been deprived of their right to make an informed decision before consenting or signing a legally binding contract. Therefore, a need is created for intermediaries to be educated of their legal duties when rendering insurance services and that will help strengthen or restore the confidence of the public towards insurance industry.

The duty of bank confidentiality and the safeguarding of financial privacy - Ahmed, Kousar Bibi (University of KwaZulu-Natal, 2024)
Abstract available in PDF.
Keywords: Banks and privacy; Customer confidentiality; Duty of confidentiality; Protection of personal information

Corporate mergers: a comparative analysis of the Italian and American legal systems - Carboni, Ludovica (LUISS Guido Carli, 2024)
Mergers in the Italian and European legal system. The Italian legal landscape for mergers. Applicable regulations. Stages of the merger process. The first phase: the merger plan. The second phase: the merger resolution. The third phase: the merger deed. The protection of creditors. The invalidity of the merger. The FIAT-Chrysler merger. Evolution of the legal nature of mergers in the Italian legal system: legislative and jurisprudential perspectives. The extinguishing-successory orientation. The evolutionary–modifying orientation. Court of cassation ruling no. 2637 of 2006. Return to the extinguishing-successory orientation: judgement no. 21970/2021. Debate surrounding judgement 21970/2021: criticism and support. Mergers in the American legal system. The American legal landscape for mergers. The evolution of the US corporate law of mergers. Sources of corporate law. The merger process. Economic motives for mergers. Steps of the merger procedure. The merger plan. Merger between parent and subsidiary or between subsidiaries. Articles of merger. Effects of merger. Abandonment of a merger or share exchange. The ExxonMobil merger. Comparative analysis of the Italian and American legal systems. Historical and constitutional influences on Italian and American legal systems. Differences and similarities in the merger process. Comparison of FIAT Chrysler and ExxonMobil mergers.

The protection of executory contracts in restructuring proceedings - Dejoux-Pasdeloup, Lea Francoise Paulette (Mikolas Romeris University, 2024)
This thesis focuses on the relationship between contract law and corporate insolvency law as it investigates the idea and protection of executory contracts within restructuring proceedings. However, preserving these agreements frequently necessitates taking legal action against established contract law tenets like the freedom of contract and the duty to perform. The study looks at how difficult it can be to keep debtor and creditor interests in balance, especially when there are disruptions brought on by insolvency. The study suggests ways to improve the efficacy of restructuring proceedings by analysing the EU Directive on restructuring and insolvency, contrasting practices in various jurisdictions, and evaluating the impact on stakeholders. The goal of this study is to protect the rights of all parties involved in corporate restructuring while advancing the creation of legal frameworks that facilitate effective restructuring.
Keywords: Creditor; Cross-border Insolvency; Darbuotojai; Debtor; Employees; Insolvency; Kreditorius; Nemokumas; Restructuring proceedings; Restruktūrizavimo bylos; Skolininkas

The Influence of Corporate Sustainability Laws on Multi-Stakeholder Initiatives to Eliminate Forced and Child Labour in Supply Chains - Fanou, Temisan (McMaster University, 2024)
An array of governance initiatives has emerged to address forced labour and labour exploitation in global value chains (GVCs). Drawing on the transnational business governance interactions theoretical framework, as well as Timothy Bartley’s place-conscious transnational governance model, this thesis examines the interaction between two of these hybrid forms of governance: multi-stakeholder initiatives and corporate sustainability laws. I conduct a case study of the cocoa sector, and specifically of the multinational company, Nestlé, using multiple qualitative research methods including legal analysis, key informant interviews, and documentary analysis. My research suggests that the layering of corporate sustainability laws, and particularly the French Duty of Vigilance Law, on top of CSR and MSIs in the cocoa sector, is not addressing the governance gap that permits corporations to evade accountability for human rights abuses in their supply chain. I find that the introduction of corporate sustainability laws may have contributed to a decrease in Nestlé's efforts to address labor violations in certain areas, while in others, it appears to have supported the continuation of existing practices. This raises implications for the continuous efforts in various jurisdictions to introduce these laws as a solution to the shortcomings of private, voluntary rule-making systems. Further research is required to explore how these governance mechanisms are interacting in other sectors, in companies of different sizes, and within various types of MSIs. This will help identify the factors that influence interactions and shed further light on the path forward for policymakers.

Squaring up with workplace bullying - Naidoo, Natashia (University of Pretoria, 2024)
Workplace bullying is not considered a form of harassment that is commonly acknowledged nor does it attract specific legislative protection. The aim of this mini-dissertation is to ascertain the degree to which victims of workplace bullying are protected by South African labour legislation and whether other measures are necessary to ensure that employees are adequately protected. A comparative analysis between South Africa and the United Kongdom's legislative frameworks that governs workplace violence and harassment and, by implication, bullying is a critical aspect of this mini-dissertation.

Taxing the digital economy: Options available for African countries - Oluwatuyi, Oluwasikemi (University of Victoria, 2024)
Tax authorities have always assessed and enforced taxes based on the physical address of businesses over the years. Nevertheless, the idea of tax jurisdiction has taken on a new meaning with the development of information and communication technology, and its profound impact on every facet of human existence – including but not restricted to trade and business. This development has undoubtedly increased capital mobility, especially in corporate form, and exposed more the weaknesses in national tax laws by enabling the artificial relocation of important economic components and potential exemption from taxes. Since it is getting harder to separate the digital economy from the rest of the economy for taxation reasons, the process of digitalization has emerged as one of the primary growth drivers. This expansion, together with aggressive tax planning strategies used by multinational enterprises (MNEs) to move revenues to low-tax jurisdictions and the development of business models requiring less physical presence, has increased the workload for tax administrators; furthermore, it has reduced governments’ capacity to raise funds in the traditional manner. In this regard, I assess how “adequate” the selected African countries’ frameworks are vis-à-vis the ongoing OECD and UN negotiations. Beyond the consultations, I call for a more inclusive and Africanised approach and the need for African countries to improve their tax administration mechanisms.
Keywords: Digital economy; International taxation; OECD; Tax